Styrene butadiene rubber as a viscosity improver: Experimental investigations and quantum chemical studies. (April 2018) - Sabarinath, S; Prabhakaran Nair, K; Rajendrakumar, PK; Parameswaran, P
The limited viscosity range of vegetable oils restricts their effectiveness as a lubricant in numerous applications. In this work, the viscosity improvement with styrene butadiene rubber as an additive in sesame oil is studied and the results are compared with those of the commonly used viscosity improver, ethyl vinyl acetate, using a rheometer. Sesame oil/styrene butadiene rubber blends show higher increment in viscosity than sesame oil/ethyl vinyl acetate blends. The viscosity variations are further validated using Arrhenius model. A computational quantum chemical software, Gaussian 09, is used to evaluate the binding energies between molecules. Ground state electronic structures of molecules are modeled with density functional theory. Thermal properties such as flash, fire, and pour points have also been evaluated for sesame oil/styrene butadiene rubber blends. Chemical oxygen demand and biological oxygen demand are the parameters chosen to evaluate the biodegradability of sesame oil/styrene butadiene rubber blend.